Analysis and assessment of the knowledge regarding to exploitation of electrical installations, risks and due to electric shock - Rektor, Natalia; Bronst, Paulina; Szabrańska, Anna; Mazur, Magdalena; Małolepsza, Aleksandra; Zach-Źródlak, Monika; Rosa, Lidia; Czechowska, Julia; Laskowski, Jakub; Kister, Klaudia (Journal of Education, Health and Sport, 2023)
INTRODUCTION This study presents the dangers due caused by electric shock and how they affect the human body. This is an important issue, because each of the recipients of this study is a user of electrical installations and the number of devices that may carry an unwanted threat is constantly increasing in every household. AIM OF STUDY The main purpose of the study is to analyze the knowledge of studied population about low-voltage electrical installations in the places of their residence, as well as the danger and consequences of electrical shock. MATERIALS AND METHODS In order to verify the level of awareness of household electrical installations users, a survey was conducted, in which participants were given the opportunity to answer questions forming three main research problems. CONCLUSION A significant part of the collected results leads to the conclusion that, on average, every second person surveyed has significant shortcomings in basic training in the safe use of electrical installations, as well as its operation and, most importantly, in providing first aid to victims. A relatively large number of respondents are not aware of the need to perform maintenance work, technical inspections and basic activities ensuring safety for them and other household members. Introduction of mandatory prevention and cyclical training, e. g. during periodic building inspections, could be one of the steps to reduce the still high rate of fatal accidents due to electric shock in Poland.